1999
DOI: 10.1128/iai.67.5.2590-2601.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Macrophage Inflammatory Protein 2 (MIP-2) and MIP-1α Attenuates Neutrophil Recruitment in the Central Nervous System during Experimental Bacterial Meningitis

Abstract: Chemokines are low-molecular-weight chemotactic cytokines that have been shown to play a central role in the perivascular transmigration and accumulation of specific subsets of leukocytes at sites of tissue damage. Using in situ hybridization (ISH), we investigated the mRNA induction of macrophage inflammatory protein 2 (MIP-2), MIP-1α, monocyte chemoattractant protein 1 (MCP-1), and RANTES. Challenge of infant rats’ brains with Haemophilus influenzae type b intraperitoneally resulted in the time-dependent exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…This observation adds the liver to the list of tissues, such as brain (Stanislaus et al, 2001), heart (Lefer et al, 1999), retina (Honjo et al, 2002), colon (Sasaki et al, 2003), synovium (Yamagata et al, 2007) and lung (Naidu et al, 2003), in which statins have been found to attenuate leukocyte infiltration. Convincing data in the literature have shown that chemokines constitute a dominating group of molecules regulating tissue accumulation of leukocytes in numerous disease models (Feng et al, 1995;Schmal et al, 1996;Diab et al, 1999;Li et al, 2004b). In the present study, we observed not only that BDL markedly increased hepatic formation of MIP-2 and KC but that pre-treatment with simvastatin also abolished cholestasis-induced CXC chemokine production in the liver.…”
Section: Discussionsupporting
confidence: 74%
“…This observation adds the liver to the list of tissues, such as brain (Stanislaus et al, 2001), heart (Lefer et al, 1999), retina (Honjo et al, 2002), colon (Sasaki et al, 2003), synovium (Yamagata et al, 2007) and lung (Naidu et al, 2003), in which statins have been found to attenuate leukocyte infiltration. Convincing data in the literature have shown that chemokines constitute a dominating group of molecules regulating tissue accumulation of leukocytes in numerous disease models (Feng et al, 1995;Schmal et al, 1996;Diab et al, 1999;Li et al, 2004b). In the present study, we observed not only that BDL markedly increased hepatic formation of MIP-2 and KC but that pre-treatment with simvastatin also abolished cholestasis-induced CXC chemokine production in the liver.…”
Section: Discussionsupporting
confidence: 74%
“…MIP-1a is known to have a role as a chemoattractant in recruiting monocytes and neutrophils to inflammation sites [35]. CCL3 is also detected in the CSF of individuals with bacterial meningitis [36] and its neutralization in experimental meningitis inhibits neutrophil recruitment to the CNS [37]. Expression of MIP-1a in the CNS could potentially attract cells and might, in part, explain the difference between P3C and LPS in causing infiltration of cells into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 (also known as CCL2) is a major chemokine that induces the recruitment and activation of monocytes, T cells, and NK cells at the early inflammatory phases (Morimoto et al 2006). MIP-2 is another important chemokine in the wound healing stages that attracts mainly polymorphonuclear granulocytes (Diab et al 1999). Down-regulation of these chemokines could therefore play a role in the improved healing seen in response to the modified surface (Schlegel et al 2011;Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%